2017
DOI: 10.1159/000464246
|View full text |Cite
|
Sign up to set email alerts
|

Right Congenital Diaphragmatic Hernias: Is There a Correlation between Prenatal Lung Volume and Postnatal Survival, as in Isolated Left Diaphragmatic Hernias?

Abstract: real membrane oxygenation (ECMO) were also evaluated. Results: In a cohort of 24 patients, O/E LHR, O/E TLV, percentage of herniated liver, and postnatal use of ECMO are not prognostic indicators of survival in the fetus with R-CDH. Cut-off values of O/E LHR of ≤ 45 or O/E TLV ≤ 25, known to select a population of severe cases for the L-CDH fetus, do not appear to extrapolate to the R-CDH fetus, as survival in both R-CDH groups is 60%. Conclusion: The findings in this study suggest that L-and R-CDH appear to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
5
11
0
1
Order By: Relevance
“…However, the anatomical difference between left and right CDH makes the application of the liver status irrelevant because the liver is almost always up in every case of RCDH. Similar to previous reports, liver herniation was observed in almost all patients with RCDH [ 9 , 14 ]. The degree of liver herniation, manifested by the percentage of the herniated liver and measured by fetal magnetic resonance imaging (MRI), was suggested as a prenatal indicator of LCDH [ 32 ]; however, the volume of the herniated liver was not found to be predictive of survival in a recent study on RCDH [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the anatomical difference between left and right CDH makes the application of the liver status irrelevant because the liver is almost always up in every case of RCDH. Similar to previous reports, liver herniation was observed in almost all patients with RCDH [ 9 , 14 ]. The degree of liver herniation, manifested by the percentage of the herniated liver and measured by fetal magnetic resonance imaging (MRI), was suggested as a prenatal indicator of LCDH [ 32 ]; however, the volume of the herniated liver was not found to be predictive of survival in a recent study on RCDH [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous reports, liver herniation was observed in almost all patients with RCDH [ 9 , 14 ]. The degree of liver herniation, manifested by the percentage of the herniated liver and measured by fetal magnetic resonance imaging (MRI), was suggested as a prenatal indicator of LCDH [ 32 ]; however, the volume of the herniated liver was not found to be predictive of survival in a recent study on RCDH [ 14 ]. We had no data on the herniated liver volume because fetal MRI data were unavailable.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Medical record information did not allow further classification by defect size, which has been noted as an important prognostic factor, particularly for morbidity at discharge (Putnam et al, ). Moreover, although right‐side CDH might have worse outcomes and different prognostic factors from left‐sided defects (Victoria et al, ), we were unable to investigate this variable. For similar reasons, the impact of liver position (intra‐ vs. extrathoracic) on survival, a known prognostic factor (Mullassery et al, ), may have been underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…(7) DeKoninck et al reported that after expectant in utero management, the survival rates in patients with RCDH and an O/E LHR of < 45% and < 30% were 17% and 0%, respectively. (21) In contrast, Victoria et al raised questions regarding the reliability of the O/E LHR as a predictor of RCDH (20). In this single-center study, the survival rate of RCDH was relatively high (up to 60%) even in patients with an O/E LHR of < 45%, probably because the results were derived from only ve cases.…”
mentioning
confidence: 83%